Alterations in the Spectrum of Spontaneous Rifampicin-Resistance Mutations in the Bacillus subtilis rpoB Gene after Cultivation in the Human Spaceflight Environment - Fajardo-Cavazos, Patricia; Leehan, Joshua D.; Nicholson, Wayne L. (Frontiers in Microbiology, 2018)
The effect of Bacillus subtilis exposure to the human spaceflight environment on growth, mutagenic frequency, and spectrum of mutations to rifampicin resistance (RifR) was investigated. B. subtilis cells were cultivated in Biological Research in Canister-Petri Dish Fixation Units (BRIC-PDFUs) on two separate missions to the International Space Station (ISS), dubbed BRIC-18 and BRIC-21, with matching asynchronous ground controls. No statistically significant difference in either growth or in the frequency of mutation to RifR was found in either experiment. However, nucleotide sequencing of the RifR regions of the rpoB gene from RifR mutants revealed dramatic differences in the spectrum of mutations between flight (FL) and ground control (GC) samples, including two newly discovered rpoB alleles in the FL samples (Q137R and L489S). The results strengthen the idea that exposure to the human spaceflight environment causes unique stresses on bacteria, leading to alterations in their mutagenic potential.